2013
DOI: 10.1128/mcb.00465-13
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination-Deubiquitination by the TRIM27-USP7 Complex Regulates Tumor Necrosis Factor Alpha-Induced Apoptosis

Abstract: bTumor necrosis factor alpha (TNF-␣) plays a role in apoptosis and proliferation in multiple types of cells, and defects in TNF-␣-induced apoptosis are associated with various autoimmune diseases. Here, we show that TRIM27, a tripartite motif (TRIM) protein containing RING finger, B-box, and coiled-coil domains, positively regulates TNF-␣-induced apoptosis. Trim27-deficient mice are resistant to TNF-␣-D-galactosamine-induced hepatocyte apoptosis. Trim27-deficient mouse embryonic fibroblasts (MEFs) are also res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 49 publications
7
86
0
Order By: Relevance
“…We have also shown that both titanium nitride and chromium disilicide nanoparticles suppress the expression of E2F8 and USP7 genes in the liver and that the effect of chromium disilicide nanoparticles on these gene expressions was more significant in comparison to the effect of titanium nitride nanoparticles. It is well known that proteins enco ding by E2F8 and USP7 genes have variable properties and can contribute to regulation of cell proliferation and apoptosis [18,25,26]. It is possible that our results can reflect the genotoxic effect of titanium nitride and chromium disilicide nanoparticles and are mostly consistent with data Ze et al [2] and Alarifi et al [8] as well as with our previous data [28,29].…”
Section: Fig 3 Effect Of Prolonged Treatment Of Mice (2 Months) By supporting
confidence: 82%
See 2 more Smart Citations
“…We have also shown that both titanium nitride and chromium disilicide nanoparticles suppress the expression of E2F8 and USP7 genes in the liver and that the effect of chromium disilicide nanoparticles on these gene expressions was more significant in comparison to the effect of titanium nitride nanoparticles. It is well known that proteins enco ding by E2F8 and USP7 genes have variable properties and can contribute to regulation of cell proliferation and apoptosis [18,25,26]. It is possible that our results can reflect the genotoxic effect of titanium nitride and chromium disilicide nanoparticles and are mostly consistent with data Ze et al [2] and Alarifi et al [8] as well as with our previous data [28,29].…”
Section: Fig 3 Effect Of Prolonged Treatment Of Mice (2 Months) By supporting
confidence: 82%
“…Moreover, low-dose cadmium has growth-promoting effects on NPrEC cells and induces transient overexpression of genes with oncogenic and immunomodulation functions, including TNF and Il13ra2 [17]. Ubiquitin specific peptidase 7 (USP7), also known as herpes virus-associated ubiquitin-specific protease (HAUSP), is hydrolase that deubiquitinates target proteins such as FOXO4, p53/TP53, MDM2, PTEN, PPARG, and other and thus participate in control of cell growth repression and apoptosis [18][19][20]. There is data that early adipogenesis is regu lated through USP7-mediated deubiquitination of the histone acetyltransferase TIP60 [21].…”
Section: We Have Studied the Effect Of Chromium Disilicide And Titanimentioning
confidence: 99%
See 1 more Smart Citation
“…Following the second mitochondrial activator of caspases (Smac)-induced cIAP autodegradation and CYLD/USP7/ USP2a-mediated K63 deubiquitination of RIP1, RIP1 is liberated from TNFR1 signaling complex I and in turn recruits the FADD adaptor and the apical caspase-8 to build a cytosolic complex II, also dubbed the Death-Inducing Signaling Complex (DISC), which mediates apoptotic cell demise. 75,76 It is noteworthy that Smac is discharged from mitochondria via mitochondrial outer membrane permeabilization (MOMP), which suggests that TNF-α-induced RIP-dependent apoptosis might occur downstream of the intrinsic mitochondrial pathway. In addition, recent studies have indicated that the lack of linear ubiquitination in complex I accelerates complex II formation in TNF signaling.…”
Section: Apoptosis Regulation By the Ubiquitin Systemmentioning
confidence: 99%
“…A role for TRIM27 has been reported in transcriptional regulation through interaction with retinoblastoma protein (RB1) and the Mi-2b-containing histone deacetylase complex in the nucleus (Krutzfeldt et al, 2005;Shimono et al, 2005), in transcriptional repression through interaction with the enhancer of polycomb protein (EPC) (Shimono et al, 2000;Bloor et al, 2005) and MBD proteins (Fukushige et al, 2006), in the negative regulation of NF-kB and IFN-signaling pathways (Zha et al, 2006), in the positive regulation of apoptosis through activation of Jun Nterminal kinase (JNK) (Dho and Kwon, 2003) and augmentation of TNF alpha receptor activation (Zaman et al, 2013), and in cell cycle regulation (Patel and Ghiselli, 2005) suggesting that TRIM27 is involved in the control of multiple cellular processes. TRIM27 has been shown to confer E3 ubiquitin ligase activity with the enzymes UBE2D1 and UBE2D3 (Napolitano et al, 2011) and to possess SUMO E3 ligase activity (Chu and Yang, 2011).…”
Section: Functionmentioning
confidence: 99%